Enhancing the Security of Software Defined Mobile Networks (SDMN) based on Blockchain Technology - G.K.Sandhia; S. Nithyaselvakumari; V. Saidulu; Nor Hissam B. Sulaiman; Anas A. Salameh (International Journal of Interactive Mobile Technologies (iJIM), 2023)
The blockchain involves future developments and new technologies. The emergence of a blockchain is a challenge for the conventional social organization and mode of activity. Data latency and mobile network capacity would no longer be a limitation for mobile users in next-generation networks of Software Defined Mobile Networks (SDMN). But there are many benefits to Software Defined Mobile Networking, it also contributes to certain security problems like DDoS / DoS attacks, unauthorized access, and single data point error. To enhance the security and privacy of the SDMN control plane, this paper proposes a new SDMN-based “Simplified Byzantine Fault Tolerance (SBFT)” algorithm to send signals between controllers and also set up an analysis study to investigate SBFT’s security and results. However, there are many benefits of Software Defined Mobile Networking (SDMN), and then it helps to resolve other security concerns including DDoS / DoS attacks, unauthorized access, and single point failure. Blockchain, an evolving revolutionary technology, will offer creative approaches to address security issues in Software-Defined Mobile networks in an efficient way. This study proposes an SDMN-based Simplified Byzantine Fault Tolerance (SBFT) for enhancing the mobile network’s security and privacy.